The Assistance Of Capital Access And Financial Governance On â€œFresh Beeâ€ Honey Business In Lumajang - Budiwati, Hesti (IMPOWERMENT SOCIETY, 2020)
The economic development and basic human needs that must be fulfilled triggered the existence of entrepreneurs group, both by productive and non-productive community. In general, because it is managed in a family or household environment, sometimes the management tends to be less serious and confused between family and business finances. From this reason, there was an interest in partnering with a honey business â€œFresh Beeâ€ owner namely Bhella Shely Afrilianti in Sumbersuko, Lumajang regency. The partner runs its business to help her family economy. The passion of partner in developing this business should be appreciated, however it requires the ability to face similar business which is quite rife. In raising Klanceng honey requires natural land because this is the advantage of Klanceng bees that its food also naturally sourced so that the honey are very high quality and a great interest to the community. The need for land is what makes this family need capital access to fulfill it. The weakness of partner mostly on financial governance which is still mixed with family finances. The implementation of this community service activity achieved the target, (1) the partnerâ€™s skill improvement in running its business in sustainable manner, (2) a simple orderly and healthy administration, which mean it is able to separate household and business finances and (3) get capital assistance from financial institutions. The intensive assistance and supervision to the partner need to be done periodically and not stop until the completion of this program. Therefore, the activeness of the team and the ranks of STIE Widya Gama Lumajang community in providing guidance to this partner needs to be carried out continuously.